2016
DOI: 10.4049/jimmunol.1601160
|View full text |Cite
|
Sign up to set email alerts
|

Correction: LFA-1/ICAM-1 Ligation in Human T Cells Promotes Th1 Polarization through a GSK3β Signaling–Dependent Notch Pathway

Abstract: In the Western immunoblot panels in Fig. 4A and 4B, phospho-and total-Akt/ERK blot panels were inadvertently presented from CD4 1 T cells purified from different donors. In the published Fig. 4A, the top blot [pAkt(Thr308)] was taken from a different donor than the middle [pAkt(Ser473)] and lower [Akt] blots, and both the pERK1/2 and ERK1/2 blots in Fig. 4B were taken from two different donors. The time-point 6 h for cell incubation on rICAM-1 was missing in the originally published legend to Fig. 4. The corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Verma et al and others demonstrated that LFA-1 signaling promoted Th1 differentiation by upregulating T-bet expression. [45][46][47][48] This result would explain the high expression of T-bet in naive T cells cultured with IFNγ-pretreated KCs in the presence of CD58/CD2 blockade ( Figure S5C). In addition, another study showed that the interaction of CD54/LFA-1 increased the phosphorylation of STAT3 and inhibited differentiation into Th2 cells.…”
Section: Discussionmentioning
confidence: 91%
“…Verma et al and others demonstrated that LFA-1 signaling promoted Th1 differentiation by upregulating T-bet expression. [45][46][47][48] This result would explain the high expression of T-bet in naive T cells cultured with IFNγ-pretreated KCs in the presence of CD58/CD2 blockade ( Figure S5C). In addition, another study showed that the interaction of CD54/LFA-1 increased the phosphorylation of STAT3 and inhibited differentiation into Th2 cells.…”
Section: Discussionmentioning
confidence: 91%
“…To test the potential impact of miR-31 function on the rearrangement of the actin cytoskeleton, we assessed the adhesion of Th1 rep cells restimulated with PMA/ionomycin in the presence of CXC motif chemokine (CXCL) 10 and Intracellular Adhesion Molecule 1 (ICAM-1), i.e., the respective ligands for CXCR3 and Lymphocyte function-associated antigen 1 (LFA-1), both of which are expressed on Th1 rep cells (44, 45). We observed an increase of ~40% in adherent Th1 rep cell number after inhibition of miR-31.…”
Section: Resultsmentioning
confidence: 99%
“…For example, LFA-1 activates GSK-3b and the g-secretase complex, which subsequently cleaves Notch-1 from the human CD4 + T cell surface [70]. The released intracellular signaling domain of Notch-1 (NICD) translocates to the nucleus and mediates the expression of the Notch-1 target genes, HEY1 and HES1.…”
Section: Lfa-1 Further Enforces the Th1 Program By Concurrently Inhib...mentioning
confidence: 99%